Changes in primary somatosensory cortex following allogeneic hand transplantation or autogenic hand replantation - Philip, Benjamin A.; Valyear, Kenneth F.; Cirstea, Carmen M.; Baune, Nathan A.; Kaufman, Christina; Frey, Scott H. (Frontiers in Neuroimaging, 2022)
Former amputees who undergo allogeneic hand transplantation or autogenic hand replantation (jointly, “hand restoration”) present a unique opportunity to measure the range of post-deafferentation plastic changes in the nervous system, especially primary somatosensory cortex (S1). However, few such patients exist, and previous studies compared single cases to small groups of typical adults. Here, we studied 5 individuals (n = 8 sessions: a transplant with 2 sessions, a transplant with 3 sessions, and three replants with 1 session each). We used functional magnetic resonance imaging (fMRI) to measure S1 responsiveness to controlled pneumatic tactile stimulation delivered to each patient's left and right fingertips and lower face. These data were compared with responses acquired from typical adults (n = 29) and current unilateral amputees (n = 19). During stimulation of the affected hand, patients' affected S1 (contralateral to affected hand) responded to stimulation in a manner similar both to amputees and to typical adults. The presence of contralateral responses indicated grossly typical S1 function, but responses were universally at the low end of the range of typical variability. Patients' affected S1 showed substantial individual variability in responses to stimulation of the intact hand: while all patients fell within the range of typical adults, some patient sessions (4/8) had substantial ipsilateral responses similar to those exhibited by current amputees. Unlike hand restoration patients, current amputees exhibited substantial S1 reorganization compared to typical adults, including bilateral S1 responses to stimulation of the intact hand. In all three participant groups, we assessed tactile localization by measuring individuals' ability to identify the location of touch on the palm and fingers. Curiously, while transplant patients improved their tactile sensory localization over time, this was uncorrelated with changes in S1 responses to tactile stimuli. Overall, our results provide the first description of cortical responses to well-controlled tactile stimulation after hand restoration. Our case studies indicate that hand restoration patients show S1 function within the range of both typical adults and amputees, but with low-amplitude and individual-specific responses that indicate a wide range of potential cortical neurological changes following de-afferentation and re-afferentation.